Assessing Managerial Discretion across Industries: A Multimethod Approach - Hambrick, Donald C.; Abrahamson, Eric (Academy of Management Journal, 1995)
Industries differ widely in how much managerial discretion, or latitude of action, they allow. This research contributes to the reliable and valid measurement of this important but hard-to-measure construct. We found that (1) a panel of academics showed very high consistency in rating managerial discretion in diverse industries, (2) a panel of security analysts agreed strongly with the academics, and (3) the panel ratings were highly related to archival indicators of discretion posited by Hambrick and Finkelstein.